A quality by design approach on pharmaceutical development of orally disintegrating tablet of Diazepam - Teixeira, João Filipe Dias (2014)
Dissertação de mestrado em Tecnologias do Medicamento, apresentada à Faculdade de Farmácia da Universidade de Coimbra